Mitochondria-targeted Ir@AuNRs as bifunctional therapeutic agents for hypoxia imaging and photothermal therapy. Issue 69 (8th August 2019) - Ke, Libing; Zhang, Cheng; Liao, Xinxing; Qiu, Kangqiang; Rees, Thomas W.; Chen, Yu; Zhao, Zizhuo; Ji, Liangnian; Chao, Hui
Abstract : Gold nanorods with surfaces modified by iridium(iii )-azo complexes (Ir@AuNRs) were developed as mitochondria-targeted bifunctional therapeutic agents for hypoxia-imaging and photothermal therapy. Abstract : Ir(iii ) complex modified gold nanorods, Ir@AuNRs, were developed as mitochondria-targeted theranostic nanoagents. Their hypoxia imaging and photothermal therapeutic properties were demonstrated in vitro and in vivo .